Devaluation of Cultural Life: A Study of Reconstruction-Resilience Practices of an Earthquake Displaced Community - Giri, Madhu (Molung Educational Frontier, 2021)
This article investigates how earthquake reconstruction was practiced without considering socio-cultural values in the dislocated community after the 2015 earthquake. The process of disaster resilience tended to focus only on technical structures like the number of houses and school buildings as the main indicators of recovery from earthquake. The resilience programs conducted by the government and NGOs did not pay due attention to caste/ethnic tensions, religious division, political clash, and cultural loss among the villagers. In this study I thus wanted to know what were the meanings/ interpretations of reconstruction and community resilience; how reconstruction programs considered socio-cultural resilience; what socio-cultural aspects in practices of reconstruction were missing, and what were the challenges of cultural resilience among the displaced communities. The study was done at Kunchok-Nabalpur of Sidhupalchok. Local people’s perspectives of reconstruction, values, cultural life (ethnographic study) and narratives were collected by using observation, interview, case study and field visit methods. The study found that caste/ethnic, religious and cultural cohesion had not been reinstalled. Socio-cultural diversity and diverse social needs of displaced people were ignored by the resilience programs of the government. This shows how technocratic reconstruction programs were not as effective as expected due to the devaluation of socio-cultural life of the disaster displaced people who otherwise could contribute to the policy and programs of sustainable and inclusive development of the society.